Social skills in adults with visual impairment - Vučinić, Vesna J; Gligorović, Milica G; Anđelković, Marija M (Sociološki pregled, 2020)
The research aim is to establish the level of acquisition of social skills in persons with visual impairment in relation to age, sex, category and time of visual impairment occurrence. The research included 131 participants with visual impairment (62.6% blind and 37.4% with low vision), both male and female, between 19 and 60 years old. In the assessment of social skills the subtest „Social Skills”, which belongs to the Adaptive Behavior Assessment System, was applied. The result analysis has established that the achievements of the majority of the participants with visual impairment belong to the category of the average. No significant relation was established between social skills and the age of the participants and the time of visual impairment occurrence, whereas the relation with the category of visual impairment and sex is statistically significant. Future research should be directed at the level of social support to persons with visual impairment for the purpose of creating more efficient support programs in the community.
Keywords: social skills; adaptive behaviour; visual impairment; blindness; low vision